(untitled) (Contemporary Journal of Social Science Review, 2025)
Objective: The focus of this study is to understand the challenges of the parents of Autistic Adolescents. Particularly the emotional, social and economic challenges with all the coping. Background: Autism Spectrum Disorder (ASD) requires a lot of care and support. Stigma, lack of proper awareness, and the lack of services sets parents of autistic on a path of suffering. Methodology:This was an exploratory qualitative study. A total of ten parents of Autistic Adolescents were interviewed and the data was systematically reviewed with the use of thematic analysis. Results:The analysis revealed the following five themes: a) Delayed diagnoses and false assumptions, b) social exclusion and the dominating stress of parenting, c) the coping phenomena (resilience) and anxiety about the future, and d) the growing monetary distress. Recommendations: Spreading awareness, lowering the costs of therapy, ease of access, centers for therapy and early diagnosis. Training for teachers, promotion of cross-disability inclusive schooling, and supportive policy to parents of Adolescents with Autism Spectrum Disorder is critical.